Strategi Komunikasi Pemasaran Destinasi Wisata Park & Farm Sipirok Melalui Media Digital Instagram Dalam Meningkatkan Minat Pengunjung - Amriul Hakim Rangkuti; Leylia Khairani (Universitas Muhammadiyah Sumatera Utara, 2023)
The development of business in the field of tourism objects is currently very rapid, giving rise to competition to reach tourists between one tourist attraction and another. Rapid changes in the business environment have forced tourist attractions to continue to be active and creative in developing existing tourist sites and continuously making updates regarding strategies in marketing them. This study aims to determine